Effects of Aqueous Extract of Zanthoxylum bungeanum on Gel Properties of Mandarin Fish (Siniperca chuatsi) Surimi Gel - Haiqiu WEI; Mingliu YANG; Yingqin ZHOU; Xubo FANG; Xiaoe CHEN; Ningning XIE (Shipin gongye ke-ji, 2023)
In this study, the effect of Zanthoxylum bungeanum aqueous extract (ZBAE) with the addition of 0, 0.125%, 0.25%, 0.5% and 1.0% on the characteristics of mandarin fish surimi gel, including water-holding capacity, gel strength, texture, whiteness, secondary structure and microstructure were performed. The results showed that the fish surimi gel's water-holding capacity, gel strength, hardness, and adhesion presented a trend of first increasing and then decreasing with the increasing of ZBAE, which had a maximum value of 0.25%. Also, FTIR analysis showed that α-helix, β-fold, and random coil structure exerted a trend of first increasing and then decreasing, and the content of β-fold and α-helix both reached the highest value at 0.125% and 0.25%, respectively. SEM results showed that when adding 0.25% ZBAE, the network structure was more ordered and denser than that of the non-addition group, and the fractal dimension, average diameter and water holes were also perfect. In addition, low addition (<0.25%) of Zant